The diagnostic certainty levels of junior clinicians: A retrospective cohort study. Issue 3 (September 2022) - Chen, Yang; Nagendran, Myura; Kilic, Yakup; Cavlan, Dominic; Feather, Adam; Westwood, Mark; Rowland, Edward; Gutteridge, Charles; Lambiase, Pier D
Background: Clinical decision-making is influenced by many factors, including clinicians' perceptions of the certainty around what is the best course of action to pursue. Objective: To characterise the documentation of working diagnoses and the associated level of real-time certainty expressed by clinicians and to gauge patient opinion about the importance of research into clinician decision certainty. Method: This was a single-centre retrospective cohort study of non-consultant grade clinicians and their assessments of patients admitted from the emergency department between 01 March 2019 and 31 March 2019. De-identified electronic health record proformas were extracted that included the type of diagnosis documented and the certainty adjective used. Patient opinion was canvassed from a focus group. Results: During the study period, 850 clerking proformas were analysed; 420 presented a single diagnosis, while 430 presented multiple diagnoses. Of the 420 single diagnoses, 67 (16%) were documented as either a symptom or physical sign and 16 (4%) were laboratory-result-defined diagnoses. No uncertainty was expressed in 309 (74%) of the diagnoses. Of 430 multiple diagnoses, uncertainty was expressed in 346 (80%) compared to 84 (20%) in which no uncertainty was expressed. The patient focus group were unanimous in their support of this research. Conclusion: The documentation of working diagnoses is highly variable among non-consultant grade clinicians. In nearly three quarters of assessments with single diagnoses, no element of uncertainty was implied or quantified. More uncertainty was expressed in multiple diagnoses than single diagnoses. Implications: Increased standardisation of documentation will help future studies to better analyse and quantify diagnostic certainty in both single and multiple working diagnoses. This could lead to subsequent examination of their association with important process or clinical outcome measures.